INITIATING ORAL ONCOLYTICS IN ZUCKERBERG SAN FRANCISCO GENERAL (ZSFG) ONCOLOGY CLINICS - HARMONIZING TEMPLATES TO CREATE STANDARD WORK FOR PATIENT EDUCATION AND FOLLOW-UP. - Wong, Piera (Oncology Nursing Forum, 2026)
Significance & Background: Zuckerberg San Francisco General (ZSFG) is the only Level 1 trauma center in San Francisco, providing primary, specialty, and acute care services, including oncology care at Ward 86. In 2022, 646 new hematologic and solid tumor cases were diagnosed at ZSFG, with the top five malignancies being non-Hodgkin lymphoma, breast, prostate, liver, and non-small cell lung cancer. A diverse patient population with varying language preferences necessitates standardized, high-quality patient education and follow-up processes for oral oncolytics. Purpose: In 2023, ZSFG's specialty pharmacy and Ward 86 nursing staff used two separate, non-standardized workflows for oral oncolytic patient education and follow-up. This resulted in: * Two different dot phrase templates, one of which lacked key patient education components. * Inconsistent follow-up practices between pharmacists and nurses, posing potential patient safety risks. By November 30, 2023, the project team aimed to harmonize the Ward 86 nursing and ZSFG specialty pharmacy patient education templates with a utilization rate of 100%. Additionally, the team sought to establish a standardized follow-up process to improve patient safety and enhance the four ZSFG True North Goals: health equity, quality, safety, and care experience. Interventions: A multidisciplinary quality improvement team was convened, including oncology nurses, pharmacists, and physicians. The team conducted a Plan-Do-Study-Act approach, including: * Process Mapping: Identified inconsistencies in patient education and follow-up documentation. * Baseline Data Collection (May-June 2023): Reviewed 21 patient education encounters; 86% were conducted by pharmacists and 14% by oncology nurses. * Intervention: Harmonization of key education components from both templates into a single standardized dot phrase and creation of a unified patient follow-up workflow. * Pilot Testing: * 1st Pilot (September 2023): Evaluated the initial harmonized template, with 100% utilization among oncology nurses (n=6) and pharmacists (n=3). * 2nd Pilot (November 2023): Finalized template and agreed upon follow-up intervals. Results: * The harmonized template was successfully adopted, achieving 100% utilization in both pilot phases. * The finalized follow-up process established structured check-ins: * Specialty pharmacists: Follow-up at one month or prior to medication refill. * Oncology nurses: Follow-up at week 1, week 2, week 3, and prior to refill. * Improved interdisciplinary collaboration. Discussion: This QI initiative successfully streamlined patient education and follow-up for oral oncolytics, improving workflow efficiency, patient safety, and interdisciplinary teamwork. A structured follow-up process was implemented, ensuring timely monitoring and adherence support for patients.